2020
DOI: 10.21203/rs.3.rs-42598/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of self-medication practices in the context of Covid-19 outbreak in Togo

Abstract: Background: To date, there is no effective treatment for Covid-19 which is a pandemic due to a new coronavirus called SARS-CoV-2. In Togo where four people in five practice self-medication, the absence of a cure for Covid-19 and its constant progression requires an assessment of self-medication patterns in the context of the pandemic. This study aimed to estimate the prevalence of self-medication to prevent Covid-19 and its associated factors in Lomé, Togo. Methods: A cross-sectional study was conducted in Lom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…The disaggregation of Hydroxychloroquine and Chloroquine from other antimalaria drugs was informed by the nonrandomized trial conducted in French which seemed to suggest a positive outcome in the treatment of COVID-19 patients, particularly those that received Hydroxychloroquine (600 mg/day) (32), and the claim by the American President, Donald Trump that he used Hydroxychloroquine to prevent COVID-19 infection (33). Like other self-medication studies (14,(19)(20)(21), our study showed that some of the participants also used antibiotics, such as Amoxicillin, Ciprofloxacin, Erythromycin, and Metronidazole either as a perceived treatment or prevention of COVID-19. In our study, 10.2% of the participants used herbal products for similar purposes.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The disaggregation of Hydroxychloroquine and Chloroquine from other antimalaria drugs was informed by the nonrandomized trial conducted in French which seemed to suggest a positive outcome in the treatment of COVID-19 patients, particularly those that received Hydroxychloroquine (600 mg/day) (32), and the claim by the American President, Donald Trump that he used Hydroxychloroquine to prevent COVID-19 infection (33). Like other self-medication studies (14,(19)(20)(21), our study showed that some of the participants also used antibiotics, such as Amoxicillin, Ciprofloxacin, Erythromycin, and Metronidazole either as a perceived treatment or prevention of COVID-19. In our study, 10.2% of the participants used herbal products for similar purposes.…”
Section: Discussionsupporting
confidence: 69%
“…From our study, the prevalence of self-medication for COVID-19 treatment or prevention was 41%. This finding was comparably higher than what was earlier reported in Togo (20). We also observed a prevalence of above 30% among respondents <24 years, that attained below tertiary education, of Islamic faith, and with insufficient knowledge of self-medication.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…There is currently no effective treatment for COVID-19 (European Centre for Disease Prevention and Control, 2020; World Health Organization (WHO), 2020a; World Health Organization, 2020b), a disease caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In Togo, Africa, four out of five people are reported to be practicing self-medication due to a shortage of physicians as well as for economic reasons (Sadio et al, 2020). Similarly, examples of self-medication practices in the setting of COVID-19 outbreaks have also been reported in Bangladesh.…”
Section: Self-medication For Coronavirus Disease 2019 (Covid-19) In D...mentioning
confidence: 99%